Buoyancy effects in steeply inclined air-water bubbly shear flow in a rectangular channel - Sanaullah, K.; Arshad, Mehmood; Khan, A.; Chughtai, I.R (Maik Nauka-Interperiodica Publishing, 2015)
We report measurements of two-dimensional (B/D = 5) fully turbulent and developed duct flows (overall length/depth, L/D = 60; D-based Reynolds number Re > 104) for inclinations to 30° from vertical at low voidages (< 5 % sectional average) representative of disperse regime using tap water bubbles (4–6 mm) and smaller bubbles (2 mm) stabilised in ionic solution. Pitot and static probe instrumentation, primitive but validated, provided adequate (10 % local value) discrimination of main aspects of the mean velocity and voidage profiles at representative streamwise station i.e L/D = 40. Our results can be divided into three categories of behaviour. For vertical flow (0°) the evidence is inconclusive as to whether bubbles are preferentially trapped within the wall-layer as found in some, may be most earlier experimental works. Thus, the 4-mm bubbles showed indication of voidage retention but the 2-mm bubbles did not. For nearly vertical flow (5°) there was pronounced profiling of voidage especially with 4-mm bubbles but the transverse transport was not suppressed sufficiently to induce any obvious layering. In this context, we also refer to similarities with previous work on one-phase vertical and nearly vertical mixed convection flows displaying buoyancy inhibited mean shear turbulence. However, with inclined flow (10+ degrees) a distinctively layered pattern was invariably manifested in which voidage confinement increased with increasing inclination. In this paper we address flow behavior at near vertical conditions. Eulerian, mixed and VOF models were used to compute voidage and mean velocity profiles.